Socialization and Education of Mount Sinabung’s Cold Lava Flood Disaster Mitigation, Karo District, North Sumatra Province - Muzambiq, Said; Nasution, Zaid Perdana; Tanjung, Munir (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This study aims to increase students' knowledge about cold lava disaster mitigation through disaster preparedness socialization activities to realize school and community disaster resilience. The methods used are in the form of exposure and explanation of the theory of lava flood mitigation, interactive discussions, giving questionnaires, interviews with qualitative analysis approaches, field trips (field education) and describing cold lava sediment material, plotting locations as well as providing direction on functions and early warning systems and emergency response. on the banks of the river (lau Borus). Involving 45 students from SMA N.1 Tiganderket in Sukatendel village, there are 10 people. The results achieved from this study indicate that the knowledge of the general public and the education community has been able to mention various types of disasters, both natural and non-natural disasters, the education community also understands natural disasters and understands explaining disaster management and has provided answers about various types of disaster management procedures. lava flood disaster and is quite good, so it is hoped that follow-up and optimal results are expected to increase students' knowledge about disaster mitigation and the realization of disaster-resilient schools and communities.